STUDI KUAT GESER TANAH DISAMPAIKAN DI DESA PASIR LOR KECAMATAN KARANGLEWAS KABUPATEN BANYUMAS (Universitas Wijayakusuma Purwokerto, 2024)
The Soil Shear Strength Study is an activity providing material that aims to provide knowledge to village residents about soil shear strength and its parameters, about the technical and mechanical properties of soil at local locations, as an effort to increase insight and knowledge. In this way, it is possible to anticipate the occurrence of shifts in the soil in the area. The method used in implementing this activity is the method of visiting and providing material or explaining material directly to the community, as well as discussions and questions and answers. The material given is about Shear Strength of Soil, which is a basic theory in soil mechanics which assumes that failure in soil is due to shear failure, namely the relative motion between soil particles. The shear strength of soil can be considered to consist of two parts, namely: Cohesion (c), namely the tensile force between soil grains which depends on the type of soil and the density of the grains, the friction part, which depends on the effective stress in the shear plane, namely the internal friction angle.The implementation of the activity of providing material on Soil Shear Strength Studies was welcomed with high enthusiasm by the participants present, both from the apparatus and the village community. This is also due to curiosity about the cause of the condition of the riverside area in this village, namely the presence of landslides along the riverbank. Given the existing conditions, the Village Head and officials ask for suggestions or input or solutions to these conditions. Future team visits are still needed by this village, in order to provide various kinds of knowledge exposure and also useful input for the progress of the village.